Philosophical Theological Analysis of Stone Jumping Culture In Nias Iman Kristina Halawa* Sekolah Tinggi Teologi Arastamar Bengkulu *imankristinahalawasttab@gmail.com Firman Jaya Hia Sekolah Tinggi Teologi Arastamar Bengkulu Abstract Culture is a characteristic that expresses the local identity of an area. Culture becomes a unifying method in each region following the beliefs held by each region. Culture is built based on the background of historical phenomena that occur and has its philosophy. - Halawa, Iman Kristina; Hia, Firman Jaya (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
Culture is a characteristic that expresses the local identity of an area. Culture becomes a unifying method in each region following the beliefs held by each region. Culture is built based on the background of historical phenomena that occur and has its philosophy. This research analyzes the philosophical value of the Nias stone-jumping tradition based on a theological perspective. This research uses qualitative research to provide understanding to the people of Nias, who are always enthusiastic about maintaining and preserving the Homba Batu culture. This research results in finding a rock jumping culture that can shape the leadership spirit of Nias' young generation based on the Bible.